Composition phytochimique et activité antioxydante des différents extraits de Rhus pentaphylla Desf. - AMMOUR, Amira; ZAAF, Souhila (My University, 2020)
Plants are the subject of many scientific studies which are constantly increasing due to their very varied active ingredients. These studies have led to phenomenal results and have led to the discovery of thousands of substances that have become indispensable to our lives. The north west of Algeria has a rich and diversified flora where many plants are not yet valued. The current study which is the subject of this thesis is part of the valorisation of an Algerian plant for the research of new bioactive molecules of plant origin. Therefore, we are interested in the phytochemical investigation and evaluation of the antioxidant activities of some extracts of a plant from the region of Oran : Rhus pentaphylla Desf. This work is a contribution to the evaluation of the antioxidant activity of the aqueous extracts of the leaves of R. pentaphylla in vitro using two methods: the 2,2-diphenyl-1-picrylhydrazyl radical scavenging (DPPH) and the reducing power test (FRAP). The extracts showed antioxidant power in the DPPH test with IC50 values ranging from 11.40 ± 0.10 mg/mL for the decoction, to 13.707 ± 0.67 mg/mL for the infusion, while in the FRAP test, the IC50 values were 13.309 ± 0.08 mg/mL for the infusion and 11.019 ± 0.1 mg/mL for the decoction of R. pentaphylla leaves. The results showed that our extracts have a significant antioxidant activity by scavenging free radicals in comparison with standard extracts. Thus, a phytochemical study represented by the quantification of polyphenols and flavonoids contents of these extracts was studied. The results showed the presence of polyphenols with quantity of 88.55 ± 5mg/mL for the infusion and 94.92 ± 7mg/mL for the decoction. Thus a high concentration of flavonoids was observed with a content of 30.9 ± 0.8 mg/mL for the infusion and 35.55 ± 0.72 mg/mL for the decoction. The high antioxidant activity of the extracts studied was strongly correlated with their high levels of polyphenols and flavonoids. Our study showed that the medicinal plant Rhus pentaphylla is very rich in phenolic compounds and has a good antioxidant activity that could be used in the pharmaceutical field as a potential source of bioactive molecules.
Keywords: Rhus pentaphylla; antioxidant activity; aqueous extract; DPPH; FRAP; polyphenols; flavonoids.